A Century of Parks Canada, 1911-2011 - Campbell, Claire (Canadian History and Environment, 2011)
"... a diverse and fascinating array of perspectives on the history of Canada's national parks, illuminating many less well-understood aspects of the evolving place of people in and near these parks." - Stephen Bocking, Professor and Chair, Environmental and Resource Studies Program, Trent University When Canada created a Dominion Parks Branch in 1911, it became the first country in the world to establish an agency devoted to managing its national parks. Over the past century this agency, now Parks Canada, has been at the centre of important debates about the place of nature in Canadian nationhood and relationships between Canada's diverse ecosystems and its communities. Today, Parks Canada manages over forty parks and reserves totalling over 200,000 square kilometres and featuring a dazzling variety of landscapes, and is recognized as a global leader in the environmental challenges of protected places. Its history is a rich repository of experience, of lessons learned - critical for making informed decisions about how to sustain the environmental and social health of our national parks. A Century of Parks Canada is published in partnership with NiCHE (Network in Canadian History and Environment; http://niche-canada.org/).